European versus Anglo-Saxon credit view: Evidence from the eurozone sovereign debt crisis - Marc Altdörfer; Carlos A. de las Salas Vega; Andre Guettler; Gunter Löffler (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2016)
We analyse whether different levels of country ties to Europe among the rating agencies Moody's, S&P, and Fitch affect the assignment of sovereign credit ratings, using the Eurozone sovereign debt crisis of 2009-2012 as a natural laboratory. We find that Fitch, the rating agency among the "Big Three" with significantly stronger ties to Europe compared to its two more US-tied peers, assigned on average more favourable ratings to Eurozone issuers during the crisis. However, Fitch's better ratings for Eurozone issuers seem to be neglected by investors as they rather follow the rating actions of Moody's and S&P. Our results thus doubt the often proposed need for an independent European credit rating agency.
urn:nbn:de:gbv:3:2-66840
Keywords: F65; G01; G14; G18; G24; H12; 330; credit rating agencies; sovereign debt crisis; rating splits; Eurozone